The Dual Dimensions of Qur’anic Revelation: Intellectual and Ethical Foundations of Contemporary Islamic Education in QS. Al-‘Alaq (1–5) and QS. ‘Abasa (1–10) - Abdul Matin Bin Salman; Wiandani, Muhammad Alfan (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2025)
This study examines the two fundamental dimensions of Qur’anic revelation as reflected in QS. Al-‘Alaq (1–5) and QS. ‘Abasa (1–10) and analyzes their relevance for contemporary Islamic education. The primary aim is to elucidate how revelation functions simultaneously as an epistemological foundation for intellectual development and as a moral guide for ethical and humanistic formation. Employing a qualitative library research design, the study analyzes the selected verses through content analysis using a thematic (maudhu‘i) tafsir approach, supported by classical and contemporary exegetical sources and scholarly literature on Islamic education. The findings indicate that QS. Al-‘Alaq emphasizes literacy, learning, and knowledge acquisition grounded in divine consciousness, while QS. ‘Abasa highlights moral sensitivity, equality, empathy, and respect for human dignity within educational interactions. Together, these revelations articulate a holistic, integrative model of Islamic education that unites intellect, spirituality, and character formation. The study implies that contemporary Islamic education should integrate cognitive excellence with ethical cultivation to address modern challenges such as moral disorientation and technocratic learning. However, the study is limited by its reliance on textual analysis and its focus on two Qur’anic passages. Future research is recommended to include empirical studies and broader Qur’anic themes to enhance practical applicability across diverse educational contexts.